2022
DOI: 10.1002/acp.4022
|View full text |Cite
|
Sign up to set email alerts
|

On the Independent Roles of Cognitive & Political Sophistication: Variation Across Attitudinal Objects

Abstract: People are motivated to maintain consistency between importantly held identities, preferences, and judgments. In political contexts, motivated reasoning can help explain a wide range of political phenomena, including extremism, polarization, and misperceptions. However, recent findings in psychology have challenged this account. These perspectives emphasize the role of cognitive sophistication (e.g., analytical reasoning, numerical literacy) in political attitudes, but differ in terms of whether it is expected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…Our finding echoes that of studies who used education as a proxy for either political sophistication or for cognitive sophistication and found that the more educated tend to be less susceptible to misinformation and to hold beliefs that run counter to scientific consensus 3,8,9,14,17,38,39 . Explanations for this have tended to either draw on the relationship between education and scientific literacy or on the fact that cognitive sophistication can favour deliberate thinking which in turn promotes accuracy in belief formation (see in particular 15,38,40 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding echoes that of studies who used education as a proxy for either political sophistication or for cognitive sophistication and found that the more educated tend to be less susceptible to misinformation and to hold beliefs that run counter to scientific consensus 3,8,9,14,17,38,39 . Explanations for this have tended to either draw on the relationship between education and scientific literacy or on the fact that cognitive sophistication can favour deliberate thinking which in turn promotes accuracy in belief formation (see in particular 15,38,40 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is either because their surveys do not contain items pertaining to political sophistication and education can be considered a proxy of political sophistication, or because they focused on cognitive sophistication rather than political sophistication as the mechanism connecting partisan cues to belief formation. There is much debate over whether political sophistication or cognitive sophistication are what connects partisan cues to belief formation 40 . We believe that our data does not allow to distinguish precisely between the two because educational attainment is a very unsatisfactory proxy of cognitive skills, especially in finegrained analyses comparing with co-variables such as political sophistication.…”
Section: Statistical Analyses and Choice Of Independent Variablesmentioning
confidence: 99%
“…Two studies in this special issue aimed to shed further light on the debate between the role of cognitive sophistication versus motivated cognition as competing theoretical accounts of why people believe in conspiracy theories. Vitriol et al (2022) found some evidence for both accounts, in that political sophistication predicted reduced endorsement of COVID‐19 conspiracy theories for Democrats (but not Republicans) whereas greater cognitive reflection was associated with reduced belief in COVID‐19 conspiracy theories regardless of partisan identity. Similarly, Saltor et al (2022) found that higher cognitive reflection, actively open minded thinking (AOT) and weaker causal illusions (as measured by a computerized contingency learning task) were all associated with the tendency to better differentiate between fake and real news about COVID‐19.…”
Section: Cognitive Processes Underlying Belief In Conspiracy Theoriesmentioning
confidence: 99%